Magnetic resonance imaging based functional imaging in paediatric oncology. (February 2017) - Manias, Karen A.; Gill, Simrandip K.; MacPherson, Lesley; Foster, Katharine; Oates, Adam; Peet, Andrew C.
Abstract: Imaging is central to management of solid tumours in children. Conventional magnetic resonance imaging (MRI) is the standard imaging modality for tumours of the central nervous system (CNS) and limbs and is increasingly used in the abdomen. It provides excellent structural detail, but imparts limited information about tumour type, aggressiveness, metastatic potential or early treatment response. MRI based functional imaging techniques, such as magnetic resonance spectroscopy, diffusion and perfusion weighted imaging, probe tissue properties to provide clinically important information about metabolites, structure and blood flow. This review describes the role of and evidence behind these functional imaging techniques in paediatric oncology and implications for integrating them into routine clinical practice. Highlights: Functional imaging probes tissue properties and complements conventional techniques. A range of functional imaging methods is increasingly used in paediatric oncology. Multimodal MRI techniques describe tissue metabolites, cellularity and blood flow. Evidence suggests imaging can inform diagnosis, prognosis and treatment response. Challenges remain in incorporating these techniques into routine clinical practice.